The antihyperlipidemic drug potassium piperonate impairs the migration and tumorigenesis of breast cancer cells via the upregulation of miR-31 - Tian, Xiaoxia; Lu, Junping; Nanding, Kathleen; Zhang, Linzhe; Liu, Yanrong; Mailisu, Mailisu; Morigen, Morigen; Fan, Lifei (Frontiers in Oncology, 2022)
Background Breast cancer is the second cause of cancer death in women, and tumor metastasis is the primary cause of mortality. Due to the involvement of many regulatory molecules and signaling pathways, the occurrence and development of metastases needs to be further studied. MicroRNAs (miRNAs) are ubiquitously expressed small non-coding RNAs that have been shown to play an important role in the diagnosis and treatment of many diseases, as well as representing an attractive candidate for metastasis control. In this study, we investigated the mechanism of potassium piperonate (GBK) in impairing breast cancer cell invasion and metastasis by targeting miR-31. Methods Breast cancer cells, either treated with GBK or left untreated, were assessed for migration and invasion capacities using wound healing and transwell assays. GBK-targeted miRNAs were identified and verified using RT-qPCR. Western blotting was used to validate the changes in expression levels of miR-31-targeted genes. Methylation specific PCR was performed to detect the effect of GBK on the methylation levels of the lncRNA LOC554202 host gene. The synergistic effect of GBK and the chemotherapy drug cisplatin (DDP) on breast cancer cells was verified using cell proliferation, colony formation, and RT-qPCR assays in vitro, and the tumor xenograft model in vivo. Results We found that miR-31 was the main target of GBK. GBK treatment affected the epigenetic modification at CpG sites by downregulating DNA methyltransferases. Thus, the CpG-associated methylation levels of lncRNA LOC554202 decreased significantly, and in turn upregulated both miR-31 and its host gene LOC554202 in breast cancer cells. We also observed the significant inhibition of miR-31-targeted genes following GBK treatment, including RHOA, WAVE3, and SATB2, with functions closely related to cancer cell invasion, migration, and proliferation. Furthermore, we revealed that the combination of GBK and DDP had a synergistic effect on inhibiting the proliferation of breast cancer cells in vitro and in vivo, especially in triple negative breast cancer (TNBC). Conclusions This study investigated the target of GBK in the inhibition of breast cancer migration and invasion, and the underlying mechanisms involved, providing theoretical support for the development of GBK as an auxiliary drug for clinical treatment.